Indirect Mitral Annuloplasty Using the Carillon Device - Krishnaswamy, Amar; Kapadia, Samir R. (Frontiers in Cardiovascular Medicine, 2020)
Patients with functional, or secondary, mitral regurgitation (FMR, SMR) often face significant symptoms that lead to functional decline as well as hospitalization and even death. Traditional mitral annuloplasty is an important treatment option for patients with FMR, but surgical risk and durability are important limitations. Percutaneous strategies are therefore a welcome alternative. The Carillon device utilizes the relationship of the coronary sinus and the mitral annulus to effect an “indirect” annuloplasty. Early series’ and recent randomized trials suggest echocardiographic and clinical benefit with a relatively straight-forward implantation technique and low rate of significant complications.